Website-Based Administrative Governance Information System in Lubuk Semantung Village - Suri Purnama Sari; Suhartini; Phinton Panglipur (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Lubuk Semantung Village is optimizing administrative governance through the implementation of a new information system. This system was developed using agile methods to adapt to rapidly changing needs. With the integration of modules such as population data management, financial management, activity documentation, and reporting, this system aims to improve efficiency and transparency. Initial results from the implementation show a significant increase in the accessibility of information for residents and the accountability of the village government. This information system is expected to be a pilot model for other villages in improving the quality of administrative governance.